2022
DOI: 10.7759/cureus.23277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oral Health Status and Communication Barriers in Hearing- and Speech-Impaired Children in Jeddah City

Abstract: Background: Hearing- and speech-impaired people form a significant part of society. Literature reveals that these people have compromised oral health conditions as compared to people with decreased levels of oral health alertness and communication barriers. The aim of the study was to assess the oral health status in hearing- and speech-impaired children in Jeddah city. Methodology: One hundred sixteen children aged five to 16 years of either gender with hearing and speech impairment were selected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The study findings indicated a higher occurrence of dental caries among children with hearing impairment, possibly influenced by factors such as age, the severity of hearing loss, and inadequate education or awareness about oral hygiene practices [ 18 ]. This aligns with previous research by Alyami et al, which reported dental caries as a common issue affecting 65% of children with hearing impairments [ 19 ]. Interestingly, there was no significant difference between genders in terms of dental caries prevalence, consistent with the study by Sandeep et al [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study findings indicated a higher occurrence of dental caries among children with hearing impairment, possibly influenced by factors such as age, the severity of hearing loss, and inadequate education or awareness about oral hygiene practices [ 18 ]. This aligns with previous research by Alyami et al, which reported dental caries as a common issue affecting 65% of children with hearing impairments [ 19 ]. Interestingly, there was no significant difference between genders in terms of dental caries prevalence, consistent with the study by Sandeep et al [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was observed that 76% of the children required prompt treatment. 8 Oral health status of 106 hearing impaired children aged 5-15 years old attending special school was assessed in Pakistan. Dental caries prevalence was 68.9% with overall mean DMFT score of 7.58±2.62.…”
Section: Oral Health Status Of Hearing-impaired Childrenmentioning
confidence: 99%
“…Vision impairment, as defined by the National Institutes of Health (NIH), is defined as a chronic impairment of vision that interferes with everyday activities and is not treatable with conventional eyeglasses or contact lenses. It is a visual issue that can cause reduced eyesight or even total blindness [ 2 ]. Almost 2.2 billion people worldwide suffer from some form of visual impairment; of those, at least 1 billion have an illness that could have been avoided or is still untreated [ 3 ].…”
Section: Introductionmentioning
confidence: 99%